PROSES SOSIALISASI BELAJAR KITAB KUNING PADA SANTRI TINGKAT WUSTHA DI PONDOK PESANTREN SALAFIYAH NURHIDAYAH DESA BENCAH KELUBI KECAMATAN TAPUNG KABUPATEN KAMPAR - Depianti, Lia; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was conducted to determine how the socialization process of learning the yellow book on students rate Wustha related to socialization patterns and the response of students to the methods of studying the yellow book in the cottage Salafiyah Nurhidayah Bencah Kelubi village Tapung subdistrict Kampar districts. Where in the yellow book learning activities of students responses are more familiar with methods sorogan compared bandongan method. To know the process of socialization associated with socialization patterns and the response of the students to the methods used, the authors conducted studies using quantitative methods with descriptive analysis. Data collection techniques used in this research is observation, guided interviews, documentation and questionnaires. The number of subject in this study were 31 respondents that all wustha level 1 class students studying the book of kuning.The results of research carried out showed that the process of socialization associated with socialization patterns of the pattern of authoritarian, democratic pattern and the pattern is permissive. Sorogan method is associated with a democratic pattern because the method sorogan students be more active, the interaction between the chaplain to students even if rudimentary. Besides, chaplain to provide guidance and direction to students so that more students to be open and willing to ask if there are lessons that are poorly understood. Whereas bandongan method is highly correlated with authoritarian pattern because with these methods more students to be passive, more dominant religious teacher in learning activities for students are not given the freedom to ask if there are lessons that are poorly understood but supervisory chaplain to students is very strict. But the response of students to the lesson quite familiar yellow book, just that the study methods are still lacking and had to be repaired because sorogan methods to improve learning outcomes more effective than the method bandongan which the majority of students are less familiar with these methods. This can be a guideline for the cleric who teaches the yellow book to replace the method bandongan with more democratic method so that the learning outcomes of studens increased.Keyword : Yellow Book, Socialization, Responses and Learning Methods